DESIGN OF PROGRAM APPLICATIONS IN THE STUDIO CENTRE PARAMOUNT FITNESS - Rully Iskandar; Sahni Damarianta P. Skom. MMSi Sahni Damarianta P. Skom. MMSi (Jurnal Sistem Informasi, 2003)
With the help of a computerized system, expectations of the author can help in termsof presenting information appropriately and accurately and is one of problem-solvingtool.With this computerized system can also as a means of storing data in an orderly, safeand doable changes or edits if necessary.With computerized system, can easily present receipcionist reports needed in a timelymanner.